Addressing eating disorders in primary care: Understanding screening recommendations and opportunities to improve care. Issue 9 (29th July 2022) - Peat, Christine M.; Feltner, Cynthia
Abstract: Objective: For the first time in its history, the United States Preventive Services Task Force (USPSTF) published a recommendation on screening for eating disorders among adolescents and adults in primary care. The current manuscript provides an overview of the USPSTF recommendation, screening principles, and suggestions for clinical and research efforts. Method: The USPSTF based their recommendations on a rigorous systematic review of the evidence on routine screening for eating disorders. Eligible studies included studies of screening test accuracy and controlled trials of screening or interventions for eating disorders in screen‐detected or previously untreated eating disorders. The current manuscript briefly summarizes the results of this evidence review which are published in full elsewhere and focuses on providing interpretation of the recommendations by clarifying the scope and methodology of the USPSTF. Results: Fifty‐seven studies were included in the evidence review. Seventeen studies evaluated screening test accuracy and 40 trials evaluated interventions among populations with previously untreated eating disorders. No studies directly assessed the benefits and harms of screening. The evidence review highlights important gaps in our knowledge regarding eating disorders in primary care. The authors provide recommendations for future studies in light of these evidence gaps and propose specific clinical strategies to improve care for those with eating disorders who present to primary care. Discussion: Primary care can play an important role in the early detection of eating disorders, but data are needed to more fully understand the potential benefits and harms of routine screening in this setting. Public Significance: There are gaps in the evidence regarding the benefits and harms of eating disorder screening in primary care. Future studies are needed to improve certainty about the net benefit of screening. Of particular importance are studies that compare routine screening to usual care (no screening). Current providers may benefit from tailored eating disorders education and training, practical tools, and integration of mental health services in primary care.